Impact of COVID-19 and related emergency measures on mental and lifestyle changes in Japanese college football players - Hideaki Waki; Masaaki Koido; Yoichi Minakawa; Shogo Miyazaki; Naruto Yoshida (Japanese Society of Physical Fitness and Sports Medicine, 2022)
This study aimed to observe the conditions of Japanese college athletes during the COVID-19 pandemic for the prevention of psychiatric and sleep disorders. A survey was conducted with 100 players before and after they refrained from sports activities due to the emergency measures (April 7-May 14, 2020) against COVID-19. The survey items used were the Hospital Anxiety and Depression Scale (HADS) for psychiatric symptoms (anxiety and depression) and the Pittsburgh Sleep Quality Index (PSQI) for sleep. A survey on the living conditions was based on a web-based questionnaire. Sleep dysfunction (PSQI ≥ 6), anxiety (HADS-A ≥ 8), and depression (HADS-D ≥ 8) were found in 20 (20%), 19 (19%), and 18 (18%) players before the emergency measures, and 32 (32%), 20 (20%), and 31 (31%) players after emergency measures, respectively. Of the 100 participants, 36 (36%) developed sleep dysfunction or depression as they lived alone, were anxious about school life (e.g., friendships), and were financially unstable regarding living expenses (e.g., not able to work part-time). Due to these findings, it is necessary to actively intervene in the mental health of university students.